Biological Characteristics and Pathogenicity of Helcococcus ovis Isolated From Clinical Bovine Mastitis in a Chinese Dairy Herd - Liu, Kai; Deng, Zhaoju; Zhang, Limei; Gu, Xiaolong; Liu, Gang; Liu, Yang; Chen, Peng; Gao, Jian; Han, Bo; Qu, Weijie (Frontiers in Veterinary Science, 2022)
Helcococcus ovis (H. ovis) was first reported in ovine subclinical mastitis milk and post-mortem examination organs in Spain and the United Kingdom in 1999; subsequently, it appeared in cattle, horse, goat, and human. However, isolation and characterization of the pathogen from clinical bovine mastitis is unknown. The objective of this study was to identify the pathogen in clinical bovine mastitis. A total of four strains were isolated from bovine mastitis milk samples from a Chinese dairy farm, and they were identified as H. ovis by microscopic examination and 16S rRNA gene sequencing. Phylogenetic tree was constructed using 16S rRNA gene, and the isolates were closely related to other China strains and strains from Japan. The growth speed of the H. ovis isolated was relatively slower than Streptococcus agalactiae, and the phenotypic characteristics were similar to H. ovis CCUG37441 and CCUG39041 except to lactose. The isolates were sensitive to most of the common used antimicrobials. The H. ovis isolates could lead to mild murine mastitis alone and induce severe mastitis when co-infected with Trueperella pyogenes in the murine mammary infection model constructed.